Effects of compression stockings during exercise and recovery on blood lactate kinetics - Rimaud, D.; Messonnier, L.; Castells, J.; Devillard, X.; Calmels, P. (European Journal of Applied Physiology, 2010)
This study aimed to investigate if wearing compression stockings (CS) during exercise and recovery could affect lactate profile in sportsmen. Eight young healthy trained male subjects performed two maximal exercise tests on a cycle ergometer on two different occasions performed randomly: CS during both exercise and recovery, and no CS. Blood lactate concentration was taken during exercise and at 0, 3, 5, 10, 15, 30 and 60 min post-exercise. The individual blood lactate recovery curves were fitted to a biexponential time function. A significantly higher blood lactate value at the end of the maximal exercise was found (12.1 ± 0.5 vs. 10.8 ± 0.5 mmol l-1) wearing CS as compared to no CS (P < 0.05). Lower c1 and higher c2 values were observed with CS during recovery, as compared to no CS. It was concluded that CS during graded exercise leads to a significant higher blood lactate value at exhaustion. Since lactate exchanges were expected to be decreased during exercise due to CS, this result was likely attributable to a higher lactate accumulation related to a greater overall contribution of anaerobic glycolysis. Although the lactate removal ability was significantly improved when wearing CS during recovery, its efficacy in promoting blood lactate clearance after high-intensity exercise is limited.